Hubungan Depresi Dan Kualitas Tidur Pada Pasien Di Puskesmas Kecamatan Penjaringan Jakarta Utara: Studi Cross-Sectional - Felicia Handoko; Surilena Hasan; Erfen Gustiawan; Nelly Tina Widjaja (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Introduction: Depression is the most common mental disorder. Depression of outpatients in primary health care is frequently unrecognized. It might affect sleep quality, which is associated with worse quality of life, poor medication adherence, higher morbidity, and mortality. The study aimed to determine the association between depression and sleep quality of outpatients in Penjaringan Primary Health Care, Jakarta. Method: This research was observational analytic using a cross-sectional approach involving 434 outpatients in Penjaringan Primary Health Care, Jakarta. The study was conducted from August until September 2019. Instruments used in this research were the demographic questionnaire, the Zung Self-Rating Depression (SDS) questionnaire, and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analytics were bivariate. Results: There were 19.1% of respondents had depression, including 12.2% mild depression, 5.8% moderate depression, and 1.2% severe depression. There were 53.5% of respondents had poor sleep quality. There was a significant relationship (p less than 0.001, OR=7.814) between depression and sleep quality in outpatients. The results also showed that depression scores were moderately correlated with sleep disturbances (r=0.434). Conclusion: This study showed a high prevalence of depression and poor sleep quality among outpatients. Depression was associated with a 7.8 times higher risk of having poor sleep quality and also correlated with the components of sleep quality especially sleep disturbance.